Efficacy of Fungicidal Seed Treatments on Seed Borne Diseases of Green Gram - Deshmukh, A. J.; Sabalpara, A. N.; Bambharolia, R. P. (International Journal of Economic Plants, 2020)
The experiment was conducted to perceive the effect of fungicidal seed treatment on seed borne diseases of green gram on susceptible cv. GM-3 with nine different fungicides. Results revealed that dry seed treatment with either mix formulation of carbendazim + mancozeb or thiophanate methyl or carbendazim @ 2.5 g kg-1 seeds is very effective in field to control Macrophomina leaf blight, Alternaria leaf spot and Anthracnose diseases. Two years pooled data indicated that PDI of Macrophomina leaf bilght was significantly lower in dry seed treatment with carbendazim + mancozeb (0.99%, 12.90%) which was statistically at par with thiophanate methyl (1.54%, 13.80%) followed by carbendazim (0.99%, 14.06%) at 35 and 65 DAS, respectively. Two years pooled data of Alternaria leaf spot indicated that the PDI of was significantly lower in dry seed treatment with carbendazim + mancozeb (2.64%, 11.15%) which was statistically at par with thiophanate methyl (2.74%, 11.30%) followed by carbendazim (2.84%, 11.37%) at 35 and 65 DAS. Two years pooled data of Anthracnose disease indicated that the PDI of Anthracnose was significantly lower in dry seed treatment with carbendazim + mancozeb (0.81%, 6.71%).